Awake and Sleep Bruxism Among Israeli Adolescents - Winocur, Ephraim; Messer, Tal; Eli, Ilana; Emodi-Perlman, Alona; Kedem, Ron; Reiter, Shoshana; Friedman-Rubin, Pessia (Frontiers in Neurology, 2019)
Introduction: Sleep and awake bruxism are potential risk factors for oral hard tissue damage, failure of dental restorations and/or temporomandibular disorders. Identifying the determinants of sleep and awake bruxism among adolescents will enable development of preventive interventions for those at risk. Objectives: To determine emotional, behavioral and physiological associations of sleep and awake bruxism among Israeli adolescents. Methods: 2,993 Israeli high school students, from five different high schools in Israel, were approached in the classroom and requested to complete online questionnaires on sleep and awake bruxism, emotional aspects, smoking, alcohol consumption, oral habits, facial pain and masticatory disturbances. The final study sample concerning awake and sleep bruxism included 2,347 participants. Results: 1,019 (43.4%) participants reported not experiencing any form of bruxism (neither sleep nor awake), 809 (34.5%) reported awake bruxism, 348 (14.8%) reported sleep bruxism and 171 (7.3%) reported both sleep and awake bruxism. Multivariate analyses (Generalised Linear Model with a binary logistic dependent variable) showed that one of the prominent variables affecting the occurrence of sleep bruxism was anxiety (mild, moderate and severe anxiety, Odds Ratios (OR) of 1.38, 2.08 and 2.35, respectively). Other variables associated with sleep bruxism were stress (each point in the stress scale increased the risk of SB by 3.2%), temporomandibular symptoms (OR=2.17) and chewing difficulties (OR=2.35). Neck pain showed a negative association (OR=0.086). Multivariate analyses for awake bruxism showed an effect of moderate anxiety (OR=1.6). Other variables associated with awake bruxism were stress (each point in stress scale increased the risk of AB by 3.3%), high and low levels of facial pain (OR=2.94 and 1.53, respectively), creaks (OR= 1.85) and oral habits (OR= 1.36). Sleep bruxism was found to be a predictor for awake bruxism, and vice versa. In both cases ORs were 8.14 . Conclusions: Among adolescents, sleep and awake bruxism are associated with emotional aspects as well as with facial pain symptoms and/or masticatory system disturbances. Awareness is recommended to decrease potential risks to teeth, dental restorations and the masticatory system.